2002
DOI: 10.1016/s0002-9440(10)64360-x
|View full text |Cite
|
Sign up to set email alerts
|

Commensal-Associated Molecular Patterns Induce Selective Toll-Like Receptor-Trafficking from Apical Membrane to Cytoplasmic Compartments in Polarized Intestinal Epithelium

Abstract: Commensal-associated molecular patterns, the major products of nonpathogenic bacteria, are present at high concentrations at the apical surface of the intestinal epithelium. However, the nature of the interaction of commensal-associated molecular patterns with the lumenal surface of the epithelium has not been defined. We have recently demonstrated that intestinal epithelial cells constitutively express several Toll-like receptors (TLRs) in vitro and in vivo that seem to be the key receptors responsible for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
205
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(218 citation statements)
references
References 38 publications
9
205
2
2
Order By: Relevance
“…TLR2 is known to be upregulated in response to peptidoglycan, lipoteichoic acid, 29 and bacterial lipoproteins 30 or LPS. TLR4 is activated by the LPS of Gram-negative bacteria 31 and LY96 is a protein associated with this receptor. The expression of these two TLR after H. pylori infection has been well documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 is known to be upregulated in response to peptidoglycan, lipoteichoic acid, 29 and bacterial lipoproteins 30 or LPS. TLR4 is activated by the LPS of Gram-negative bacteria 31 and LY96 is a protein associated with this receptor. The expression of these two TLR after H. pylori infection has been well documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that IEC are poorly responsive to Gram-positive bacterial cell wall components and other TLR2 ligands. Studies have demonstrated that IEC express TLR2 mRNA but the functional significance of these findings are unclear (71)(72)(73). A recent study using immunohistochemistry demonstrated that lamina propria macrophages express TLR2 and that expression increases with inflammation (74).…”
Section: Human Intestinal Epithelial Cells Are Broadly Unresponsive Tmentioning
confidence: 99%
“…This finding is in line with the fact that toll-like receptors on immune and epithelial cells can recognize specific bacterial components from dead cells [27]. Despite viability being a requirement of a probiotic per the World Health Organization definition, use of attenuated probiotics could be advantageous due to compliance with regulatory demands, which include microbiological stability, as well as leading to a longer shelf-life of the final product.…”
Section: Discussionmentioning
confidence: 61%